Analysis of Matrix on Dynamic Resource Management for Application of Manpower Sustainability in an Oil and Gas Company in the United Arab Emirates - Farha, Mohd Ghazali (2021)
Companies comprising of clients, consultants or contractors, in trying to execute multiple projects concurrently, face the challenge of getting the right people for the job or risk cost over-run due to mismanaging resources. Cost, time and quality of the finished product seems to be governed by the project management techniques, policy changes unstable demand and supply in this industry. The objective of this study is to identify and propose a matrix for organizations to manage projects with limited resources and changing policies, focused on the human capital. The basic design of this study uses extracted experiential information and cross-references it with reviewed literature. Secondary data will assist in further triangulating the hypothesis towards the process gap which leads to resource wastage. This study analyses five key elements in resource management; namely the aging workforce, working tools, knowledge management practices, workforce localisation , and policy shifts effecting the generational gap. Findings indicate that the five elements have an equal correlation in producing optimal results. Research question 1 found a big value to retain the retirees and senior employees for their skills sets, knowledge, patience and experience leading to a sustainable productive project management. Research question 2 found that the digital tools and technology is sufficient but needs continuous training to optimise the use. Research question 3 highlighted that tacit knowledge is best shared via mentorship and internal working groups, intrinsic knowledge is best attained via e-learning. Research question 4 indicates a high importance of assessing the efforts of workforce localization as the robust working environment and requirements of the Oil and Gas industry in not matching the expected productivity outcome and skillsets of the local talents. Researchquestion 5 found that the project governance and organizational policies must be aligned to facilitate generational inclusiveness. Project management systems need to address continuity issues. Digitalization of the organization is the heart of the dynamic resource management. From the Matrix of Dynamic Resource Management, four initiatives are proposed towards better human capital development. Remote working regardless of time is the new norm after the COVID-19 pandemic. Innovation in communication, documentation and learning encourages company growth and benefits to everyone. Technology has helped reduce human error, save time and manpower costs. Strategic actions such as re-tooling the Human Capital, and optimising the knowledge of the aging workforce will ensure better practices for the industry.